Evaluating the first year roll-out of the Imibala Gifted And Talented Enrichment Programme of the Imibala Trust in The Western Cape - Reddy, Lucina Jacqueline (Institute for Monitoring and Evaluation, 2016)
The following dissertation details an evaluation conducted on a giftedness programme. The introduction of giftedness programmes can be traced as far back as 1922 where Terman was one of the first people to document and formalise the link between one's innate ability and their performance on a number of outcomes. Since then many other theorists Renzulli (1977) and Subotnik, Olszewski-Kubilius, and Worrell (2011) have expanded on the definition of giftedness to include not only one's innate ability but development of potential through a specialised environment that encourages the gifted learner to enhance their ability. In 2013, a programme evaluation student at the University of Cape Town, Reitumetse Mogorosi, conducted research for the Imibala Trust to assist with the design of the Gifted and Talented Enrichment (GATE) Programme. The Imibala Trust had for some time (with the support of the Metropole East Education Department) decided to pilot such a programme that aimed to serve gifted disadvantaged children in the Helderberg region. As a result of Mogorosi's work the GATE personnel were provided with an evaluation report that detailed a plausible programme theory for their programme; the activities that the GATE programme should include in its design; the selection process to be followed to recruit the identified target audience; and the importance of engaging relevant stakeholders in the programme. Following Mogorosi's (2014) report, the GATE programme was piloted in 2014. In 2014, a second masters' student from the University of Cape Town evaluated the pilot implementation of the GATE programme. This dissertation is an account of that evaluation study. The evaluator conducted two forms of evaluation, namely a process evaluation and a short-term outcome evaluation. The process evaluation aimed to establish whether the GATE personnel had implemented the programme as planned; while the short-term outcome evaluation aimed to determine whether the participants in the GATE programme perceived any changes as a result of the programme.